A PET study in healthy subjects of brain exposure of 11C-labelled osimertinib – A drug intended for treatment of brain metastases in non-small cell lung cancer. Issue 4 (April 2020) - Varrone, Andrea; Varnäs, Katarina; Jucaite, Aurelija; Cselényi, Zsolt; Johnström, Peter; Schou, Magnus; Vazquez-Romero, Ana; Moein, Mohammad M; Halldin, Christer; Brown, Andrew P; Vishwanathan, Karthick; Farde, Lars
Osimertinib is a tyrosine kinase inhibitor (TKI) of the mutated epidermal growth factor receptor (EGFRm) with observed efficacy in patients with brain metastases. Brain exposure and drug distribution in tumor regions are important criteria for evaluation and confirmation of CNS efficacy. The aim of this PET study was therefore to determine brain distribution and exposure of 11 C-labelled osimertinib administered intravenously in subjects with an intact blood–brain barrier. Eight male healthy subjects (age 52 ± 8 years) underwent one PET measurement with 11 C-osimertinib. The pharmacokinetic parameters C max (brain) (standardized uptake value), T max (brain) and AUC 0–90 min brain/blood ratio were calculated. The outcome measure for 11 C-osimertinib brain exposure was the total distribution volume ( V T ). 11 C-osimertinib distributed rapidly to the brain, with higher uptake in grey than in white matter. Mean C max, T max and AUC 0–90 min brain/blood ratio were 1.5 (range 1–1.8), 13 min (range 5–30 min), and 3.8 (range 3.3–4.1). Whole brain and white matter V T were 14 mL×cm −3 (range 11–18) and 7 mL×cm −3 (range 5–12). This study in healthy volunteers shows that 11 C-osimertinib penetrates the intact blood–brain barrier. The approach used further illustrates the role of molecular imaging in facilitating the development of novel drugs for the treatment of malignancies affecting the brain.